2021
DOI: 10.36959/472/360
|View full text |Cite
|
Sign up to set email alerts
|

Tabularised Incised Plate (TIP) Urethroplasty in Narrow V/S Wide Urethral Plate: A Comparative Study in a Developing Country Perspective

Abstract: Introduction: Tubularized incised plate (TIP) urethroplasty is the most commonly performed operation for distal and mid shaft hypospadias. There are controversies in the previous reports regarding the association between urethral plate width and complications in TIP repair. The aim of this study was to compare the impact of urethral plate width in TIP repair on the development of complications in the perspective of a developing country.Methods: It was a prospective comparative study carried out in the departme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
1
2

Year Published

2021
2021
2022
2022

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(3 citation statements)
references
References 28 publications
(42 reference statements)
0
1
2
Order By: Relevance
“…However, the use of a numerical cutoff to demark urethral plate quality may be of limited utility, since Walid et al . recently showed that plate width gradually increases with age 22 . In contrast, our results obtained with the POST scoring system did not relate to patient age, thus supporting use of this tool as a reliable indicator of urethral plate quality across age groups and physical dimensions.…”
Section: Discussioncontrasting
confidence: 43%
See 1 more Smart Citation
“…However, the use of a numerical cutoff to demark urethral plate quality may be of limited utility, since Walid et al . recently showed that plate width gradually increases with age 22 . In contrast, our results obtained with the POST scoring system did not relate to patient age, thus supporting use of this tool as a reliable indicator of urethral plate quality across age groups and physical dimensions.…”
Section: Discussioncontrasting
confidence: 43%
“…21 However, the use of a numerical cutoff to demark urethral plate quality may be of limited utility, since Walid et al recently showed that plate width gradually increases with age. 22 In contrast, our results obtained with the POST scoring system did not relate to patient age, thus supporting use of this tool as a reliable indicator of urethral plate quality across age groups and physical dimensions. At the same time, POST scores did still correlate with pre-incision urethral plate width in our cohort, confirming that POST scores do, indeed, provide a realistic reflection of urethral plate width as well.…”
Section: Discussioncontrasting
confidence: 43%
“… 8 , 9 Walid et al noted that urethral plate width increases with age, making definitive cut-off values unsuitable for defining a favorable urethral plate. 10 POST instead permits objective measurement of hypospadias severity, and urethral plate quality in particular, prior to complete physiological retraction of the prepuce ( Figure 2 ), but without significant influence of patient age on assessment outcome. Therefore, the POST system can be used in outpatient clinics to help surgeons guide decision-making objectively, inform surgical planning, and assist with appropriate parent counselling.…”
Section: An Aid For Objective Preoperative Assessment and Parental Counselingmentioning
confidence: 99%